Social Justice Identity and Program Evaluation: A Pilot Study of CMHC Students - Heidi L. Henry (Teaching and Supervision in Counseling, 2024)
Program development and evaluation can be used to address historical inequities in mental health, but they are scarcely studied in counselor education. The purpose of this pilot study was to examine how taking one social-justice focused CMHC management course impacted 66 counseling students’ social justice identity and program evaluation understanding. Participating students completed a group program proposal focused on social justice and program evaluation. To assess change in their social justice attitudes, behaviors, and program evaluation understanding, they completed a demographic questionnaire, pre-test, and post-test. The results, derived from t-tests and Wilcoxon Signed-Rank tests, indicated a significant improvement from pre- to post-test in social justice self-efficacy, interest, and program evaluation understanding. Limitations, implications, and suggestions for future research are discussed.
Keywords: program evaluation; social justice identity; clinical mental health counseling; groupwork